Impact of Climate Change and its Various Aspects in the Indian Context: Challenges and Opportunities for India's Sustainable Future (Journal of Advances and Scholarly Researches in Allied Education, 2023)
There are several ways in which India is experiencing climate change impacts. Risingtemperatures have had detrimental implications on agriculture and human health. Changes in precipitationpatterns have had an impact on water availability and agricultural stability. Residents and infrastructure incoastal areas are vulnerable to the effects of sea level rise and extreme weather. Glacial melt in theHimalayas is having an impact on river flow, which has repercussions for water supply and electricalgeneration. Moreover, those who already face socioeconomic disadvantages are placed at even greaterdanger due to climate change. India's long-term development and prosperity depend on its ability toadapt to and mitigate these risks.